Diterpenoid trigonoreidon B isolated from Trigonostemon reidioides alleviates inflammation in models of LPS-stimulated murine macrophages and inflammatory liver injury in mice - Utaipan, Tanyarath; Suksamrarn, Apichart; Kaemchantuek, Praphakorn; Chokchaisiri, Ratchanaporn; Stremmel, Wolfgang; Chamulitrat, Walee; Chunglok, Warangkana (Biomedicine & pharmacotherapy, 2018)
The roots of Trigonostemon reidioides, Thai medicinal plant, have long been used as an antidote, laxative, and antiasthmatic, and also used as folk remedy for relieving inflammatory symptoms from poisonous insect and snake bites as well as abscesses and sprains. Here, we studied anti-inflammatory effects of a major diterpenoid named trigonoreidon B (TR-B) isolated from T. reidioides roots in lipopolysaccharide (LPS)-activated RAW264.7 macrophages and D-galactosamine (D-GalN)/LPS-induced inflammatory liver injury in mice. RAW264.7 cells were treated with TR-B or other available minor diterpenoids, and cell viability was determined by AlamarBlue. The levels of inflammatory mediators were determined by nitrite assay, ELISA, and luminescence. NF-κB nuclear translocation was investigated by indirect immunofluorescence. Expression levels were determined by real-time PCR and Western blotting. Transaminases and caspase activities were determined by using assay kits. Our results showed that TR-B was able to suppress PI3K/Akt activation and inflammatory induction in LPS-activated macrophages. These events were concomitant with TR-B’s ability to hamper activated generation of reactive oxygen species, nitric oxide, prostaglandin E2, and cytokines as well as NF-κB p65 nuclear translocation. In an in vivo model of inflammatory liver injury, an administration of TR-B protected mice from D-GalN/LPS-induced liver injury by suppressing the elevation of serum TNF-α, transaminase activities, and hepatocyte apoptosis as well as an improvement of liver histopathology. During protection against liver damage, TR-B also prevented the loss of Akt phosphorylation. Collectively, the results of this present study suggested that TR-B exerted an anti-inflammatory effect via attenuating macrophage-mediated inflammation and inflammatory liver injury in vivo. TR-B may represent a promising lead compound for anti-inflammatory drug development.
Gesehen am 27.02.2020